Biological performance of grape varieties in Eastern Hungary - Rakonczás, N. (International Journal of Horticultural Science, 2015)
Eurasian and interspecific grape varieties and candidates were inspected for biological productivity in the variety collection of the University of Debrecen at the Horticultural Experimental Station in Pallag. In this paper, data are reported on yields (kg/stock), cane production (kg/ stock) and use-up index of wood yield of each cultivar in the experimental years 2011-2012. From the range of Eurasian (Vitis vinifera L.) white wine-grape qualified cultivars and candidates ’Ezerfürtû’, ’Generosa’, ’Jubileum 75’, ’Müller Thurgau’, ’Zöld veltelíni’,’B-11’, ’CSFT-92’, ’Pintes’, from the range of Eurasian (Vitis vinifera L.) red wine-grape qualified cultivars and candidates ’Kármin’, ’Pinot noir’, ’Alicante Bouschet’ and ’Rubintos’ were highlighted. Promising data of interspecific ’Aletta’, ’Csillám’, ’Kunleány’, ’Orpheus’, ’Refrén’, ’Taurus’, ’Viktória gyöngye’, ’Alföld 100’, ’Reform’, ’RF38/32’, ’Toldi’ white, and ’Dunagyöngye’ ’Pannon frankos’ red wine-grape cultivars and candidates were emphasized. Published data refer only to the biological performance of the cultivars. The thorough evaluation of varieties needs respect to data on resistance to fungal disease and climatic extremities, and other characteristics concerning production technology and oenological parameters.